A derivative-free multistart framework for an automated noncoplanar beam angle optimization in IMRT - Rocha, Humberto (2016)
The inverse planning of an intensity-modulated radiation therapy (IMRT) treatment requires decisions regarding the angles used for radiation incidence, even when arcs are used. The possibility of improving the quality of treatment plans by an optimized selection of the beam angle incidences-beam angle optimization (BAO)-is seldom done in clinical practice. The inclusion of noncoplanar beam incidences in an automated optimization routine is even more unusual. However, for some tumor sites, the advantage of considering noncoplanar beam incidences is well known. This paper presents the benefits of using a derivative-free multistart framework for the optimization of the noncoplanar BAO problem.